Optimasi Penjadwalan Menggunakan Metode Algoritma Genetika di Sekolah Menengah Kejuruan Annuqayah - Sumenep - Nirwana Haidar Hari; Fauzan Prasetyo Eka Putra; Hamdlani Hamdlani (Program Studi Sistem Informasi, 2018)
The problem faced by the Annuqayah Vocational School curriculum is the same schedule and is taught by the same teacher. Such problems are quite complex problems because they relate to the number of teachers available. The lesson schedule is presented in the form of day and class hours tables. The subject can be seen that every day schedule divided into time slots. Each time slot has a list of subjects taught by the teacher in a particular room. To optimize the lesson schedule in Annuqayah Vocational School, Genetic Algorithm is used. This algorithm is a computational approach to the principle of natural selection, Charles Darwin's theory of evolution and the theory of Mendel's inheritance [1]. The optimization process in Genetic Algorithms includes individual generation, evaluation of fitness values, determination of probability values, Roulette Wheel selection, crossover, mutations, and new individual generation. Scheduling optimization using the Genetic Algorithm approach was declared successful because it was able to find the right combination of scheduling with optimal fitness values in 10 attempts, and no violations of the established rules from the curriculum were found so that it could assist in the preparation of subject schedules in Annuqayah Vocational High School.Keywords: curriculum, Vocational High School, scheduling, Genetic Algorithm, optimization.